DELAY RISK ASSESSMENT IN CRUSHER SYSTEM CONSTRUCTION AT PT FREEPORT INDONESIA UNDERGROUND MINE - Bambang Eka Muliano; Idqan Fahmi; Yudha Heryawan Asnawi (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2021)
The construction of a crusher system is a very important sequence in the underground mining stage. Therefore, the delays in completing construction will have a negative effect on production achievement. Of the three crusher systems with a capacity of around 2,500 tons per hour that have been completed to support the development of a new underground mine at PT Freeport Indonesia (PTFI), two of them have experienced a delay in completion of more than one month while the remaining one was completed faster. This study aims to assess the risk of delays in the construction of a crusher system in PTFI’s underground mine. The risk of delay was identified and registered from the history of the construction reports of the three previous crusher systems. Then the opinions of 35 selected experts are collected to provide an assessment on four scales of both consequences and likelihood scores. This expert assessment is used for risk analysis to determine the severity level of each risk. The result of this study identified 79 risks of delay in the construction of a crusher system in PTFI’s underground mine which can be grouped into five categories: 16 risks related to work area, 8 risks related to construction drawing, 22 risks related to materials, 3 risks related to administration, and 30 risks related to resources. From the results of risk analysis and evaluation, it was found that 17 risks of high severity delays required risk treatment: 1 risk in the work area, 11 risks to material, and 5 risks to resources. In very specific projects such as the construction of a crusher system in a remote underground mine, the risks related to materials and resources management are of high severity impact for project delays. Keywords: construction delay analysis, construction failure case studies, construction risk assessment, project risk management